Expression of killer cell immunoglobulin-like receptors (KIR) in sex-associated malignancies - Hassan, Norfarazieda; Lee, Le Jie; Tan, Jun Hao; Idris, Siti Zuleha; Mohd Ibrahim, Hishamshah; Osman, Raudhawati; Seow, Heng Fong; Mohtarrudin, Norhafizah; Andi Asri, Andi Anggeriana; Abdullah, Maha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Sex shapes immune response with possible consequence on tumor immune escape. Acute lymphoblastic leukemia (ALL) predominates in males while ovarian cancer (OC) occurs in females. NK cells essential for tumor killing may have male preponderance. Association of sex, NK cell activity and malignancies is unclear. We hypothesize that sex differentially affects KIR expressions in sex-biased cancers. Method: Expression of inhibitory (KIR2DL1-5 and KIR3DL1-3) and activating (KIR2DS1-2 and 4-5 and KIR3DS1) genes in B-, T-cell ALL, OC and normal controls were determined by reverse-transcription polymerase-chain-reaction. Result: All normal males (but not females) expressed the framework genes and generally maintained haplotype A, except KIR3DL1. Normal females expressed more activating KIRs. Frequencies of KIR2DL1, 2DL4 and 2DS2 were significantly reduced among ovarian cancer patients. Sex difference in frequencies of KIR expression was not detected in ALL as majority were undetectable except framework gene KIR3DL2, was more frequent among T-ALL. Conclusion: Cancers may be associated with reduced KIR expression and influence of sex requires investigation.